Population based cost utility study of interferon beta-1b in secondary progressive multiple sclerosis. Issue 7224 (11th December 1999) - Forbes, Raeburn B; Lees, Ann; Waugh, Norman; Swingler, Robert J
Abstract: Objective: To evaluate the cost utility of interferon beta-1b in secondary progressive multiple sclerosis. Design: Population based cost utility model (healthcare perspective). Data on use of health services were obtained from case records and routine morbidity data and utility values from a EuroQol survey. Local and published costs were used. Effectiveness was modelled using data on relative risk reductions from a randomised trial of interferon beta-1b. Setting: Tayside region, 1993-5. Subjects: 132 ambulatory people with secondary progressive multiple sclerosis. Main outcome measures: Cost per quality adjusted life year (QALY) gained. Rate of relapse and proportion becoming wheelchair dependent over three years. Results: The number needed to treat for 30 months to delay time to wheelchair dependence in one person by nine months was 18 (95% confidence interval 5 to 26). For every 18 people treated for 30 months, six relapses would be prevented, gaining 0.397 discounted QALYs. The cost per QALY gained was £1 024 667 (£276 466 to £1 485 499). If treatment was restricted to patients attending neurology services, the number needed to treat was 14 (cost per QALY gained £833 514 (£161 358 to ∞)). The cost per QALY gained was not sensitive to changes in cost which took account of a societal perspective. Conclusions: The cost per QALY gained from interferon beta is high because of the high drug cost and modest clinical effect. Resources could be used more efficiently elsewhere.